A new role of growth hormone and insulin growth factor receptor type 1 in neonatal inflammatory nociception. (July 2017) - Manzano-García, Alfredo; Gamal-Eltrabily, Mohammed
Abstract : Abstract: Growth hormone (GH) and insulin growth factor 1 (IGF1) are implicated in nociceptive processing; it has been reported that the latter participates in neonatal inflammatory nociception. In the target article, the authors propose that local inflammation evoked by carrageenan administration in mice produces a decrease in the local GH levels and an increment of IGF1 receptors type 1 expression, this produces behavioral nociception and peripheral sensitization that can be prevented by GH systemic administration pretreatment. Abstract : Neonatal inflammation produces nociception by a local decrease of growth hormone and an increment of the insulin growth factor 1-1R. Systemic growth hormone prevents the development of nociception.